2022
DOI: 10.1097/bth.0000000000000423
|View full text |Cite
|
Sign up to set email alerts
|

Initial Outcomes of a Novel Modification of Looped Threaded Carpal Tunnel Release Method

Abstract: Various surgical techniques are available for the alleviation of symptoms in carpal tunnel syndrome and each of them has its pros and cons. This study was designed and performed to present a novel approach for cutting transverse carpal ligament by the thread looping technique without the use of ultrasonography. The novel modification of looped threaded carpal tunnel release was performed on 10 hands of 10 patients. The disabilities of arm, shoulder, and hand score, visual analog scale, and 2-point discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that TCTR provides better outcomes, faster recovery, and quicker return to work than open CTR or endoscopic CTR [13,14,15,16]. Most patients experienced a reduction in pain within 12 h after TCTR.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported that TCTR provides better outcomes, faster recovery, and quicker return to work than open CTR or endoscopic CTR [13,14,15,16]. Most patients experienced a reduction in pain within 12 h after TCTR.…”
Section: Discussionmentioning
confidence: 85%
“…The incidence of ulnar side branching of the recurrent motor branch has been reported to be as high as 3 %, and this can be identified using US [23]. The use of a looped TCTR without US guidance, as recently reported [16], may therefore bear a potential risk of nerve injury.…”
Section: Parametersmentioning
confidence: 88%